Endocrine-Disrupting Effects of Bisphenol A on the Cardiovascular System: A Review - Maria Inês Fonseca; Margarida Lorigo; Elisa Cairrao (Journal of Xenobiotics, 2022)
Currently, the plastic monomer and plasticizer bisphenol A (BPA) is one of the most widely used chemicals. BPA is present in polycarbonate plastics and epoxy resins, commonly used in food storage and industrial or medical products. However, the use of this synthetic compound is a growing concern, as BPA is an endocrine-disrupting compound and can bind mainly to estrogen receptors, interfering with different functions at the cardiovascular level. Several studies have investigated the disruptive effects of BPA; however, its cardiotoxicity remains unclear. Therefore, this review’s purpose is to address the most recent studies on the implications of BPA on the cardiovascular system. Our findings suggest that BPA impairs cardiac excitability through intracellular mechanisms, involving the inhibition of the main ion channels, changes in Ca2+ handling, the induction of oxidative stress, and epigenetic modifications. Our data support that BPA exposure increases the risk of developing cardiovascular diseases (CVDs) including atherosclerosis and its risk factors such as hypertension and diabetes. Furthermore, BPA exposure is also particularly harmful in pregnancy, promoting the development of hypertensive disorders during pregnancy. In summary, BPA exposure compromises human health, promoting the development and progression of CVDs and risk factors. Further studies are needed to clarify the human health effects of BPA-induced cardiotoxicity.